Sex and poverty modify associations between maternal peripartum concentrations of DDT/E and pyrethroid metabolites and thyroid hormone levels in neonates participating in the VHEMBE study, South Africa. (October 2019) - Chevrier, Jonathan; Rauch, Stephen; Obida, Muvhulawa; Crause, Madelein; Bornman, Riana; Eskenazi, Brenda
Abstract: Indoor Residual Spraying (IRS), the application of insecticides on the inside walls of dwellings, is used by 84 countries for malaria control. Although effective in preventing malaria, this practice results in elevated insecticide exposure to >100 million people, most of whom are Africans. Pyrethroid insecticides and dichlorodiphenyl trichloroethane (DDT) are currently used for IRS. Animal and in vitro studies suggest that pyrethroids and DDT interfere with thyroid hormone homeostasis but human studies are inconsistent and no prior study has investigated this question in a population residing in an area where IRS is conducted. Our objective was thus to evaluate whether prenatal exposure to pyrethroids, DDT or DDT's breakdown product dichlorodiphenyl dichloroethylene (DDE) is associated with altered thyroid hormone levels among neonates from Limpopo, South Africa, where pyrethroids and DDT are used annually to control malaria. We measured serum DDT/E and urinary pyrethroid metabolite concentrations in maternal peripartum samples from 717 women participating in the Venda Health Examination of Mothers, Babies and their Environment (VHEMBE), a birth cohort study conducted in Limpopo's Vhembe district. We measured total thyroxine (T4) and thyroid-stimulating hormone (TSH) in dried blood spots collected via heel stick. We found that all pyrethroid metabolites were positively associated with TSH; trans -DCCA and 3-PBA showed the strongest associations with a 12.3% (95%CI = 3.0, 22.3) and 14.0% (95%CI = 0.5, 30.2) change for each 10-fold increase in biomarker concentration, respectively. These associations were substantially stronger among children from households below the South African food poverty line. DDT and DDE were associated with lower total T4 among boys only (β = −0.27 μg/dL per 10-fold increase; 95%CI = −0.47, −0.04). Results suggest that prenatal exposure to DDT, DDE and pyrethroid insecticides is associated with changes in neonatal thyroid hormones consistent with hypothyroidism/hypothyroxinemia and that sex and poverty modify associations. Further research is needed to confirm these findings and examine whether they have implications for child development. Highlights: Indoor Residual Spraying (IRS) is used by 84 countries to control malaria. There are limited data on the potential adverse health effects of IRS insecticides. Maternal serum DDT and DDE concentrations were associated with lower T4 in male neonates but not in females. Maternal urinary pyrethroid metabolites were related to higher TSH in neonates. Associations with TSH were stronger among neonates from poor households.